2004
DOI: 10.1016/j.febslet.2004.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Allele‐specific transcript isoforms in human

Abstract: Estimates of the number of human genes that produce more than one transcript isoform through alternative mRNA splicing depend on the assumption that the observation of multiple transcripts from a gene can be attributed entirely to alternative splicing. It is possible, however, that a substantial proportion of cases where multiple transcripts have been observed for a gene result from differences between alleles. Many examples of genes that are spliced differently from different alleles have been reported but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
(44 reference statements)
6
32
0
Order By: Relevance
“…Previous studies based on exon tiling microarray experiments provided evidence that a subset of single-nucleotide polymorphisms (SNPs) located within exons or neighboring intronic sequences are associated with individual-specific variation in alternative splicing levels (Kwan et al 2008; for review, see Graveley 2008). Using RNA-Seq data from cerebellar cortex tissue samples from six individuals, Wang et al (2008) estimated that 10%-30% of alternative splicing events exhibited interindividual-specific variability, which is in agreement with a previous estimate of ;21% (Nembaware et al 2004). Moreover, it was estimated that individual-specific variation in alternative splicing is twofold to threefold less frequent than tissue-dependent variation in alternative splicing .…”
Section: Cell- Tissue- and Individual-specific Transcript Variantssupporting
confidence: 75%
“…Previous studies based on exon tiling microarray experiments provided evidence that a subset of single-nucleotide polymorphisms (SNPs) located within exons or neighboring intronic sequences are associated with individual-specific variation in alternative splicing levels (Kwan et al 2008; for review, see Graveley 2008). Using RNA-Seq data from cerebellar cortex tissue samples from six individuals, Wang et al (2008) estimated that 10%-30% of alternative splicing events exhibited interindividual-specific variability, which is in agreement with a previous estimate of ;21% (Nembaware et al 2004). Moreover, it was estimated that individual-specific variation in alternative splicing is twofold to threefold less frequent than tissue-dependent variation in alternative splicing .…”
Section: Cell- Tissue- and Individual-specific Transcript Variantssupporting
confidence: 75%
“…Thus, it is postulated here that allele-dependent splicing phenomenon is not uncommon in the human population, but it seems that splice SNPs exert their impact rather through complex effects. A recent survey showed association of 21% alternatively spliced genes with closely linked SNPs (Nembaware et al, 2004) and among these events, there is evidence of two different types of allelespecific splicing: 1) pure (complete) allele-dependent splicing, in which one allele gives rise to one isoform and another results in the alternative form (as detected in the present study). This type was later suggested to be less common (Nembaware et al, 2008).…”
Section: Current Understanding Of Allele-dependent Splicingmentioning
confidence: 53%
“…Deep sequencing of necroptic samples obtained from multiple tissues suggested that between *10 and 30% of alternative transcript events may show individual-specific variation ) and the existence of a considerable fraction of genome variability that influence pre-mRNA processing was supported by previous studies (Graveley 2008;Kralovicova et al 2004;Nembaware et al 2004;Pagani and Baralle 2004;Wang et al 2008). Therefore, it should be fruitful to employ mRef sequencing to identify disease susceptibility and protective haplotypes containing low-inclusion TE pseudoexons that may modulate expression of natural transcripts and disease risk.…”
Section: Implications For Complex Trait Geneticsmentioning
confidence: 81%